THE INFLUENCE OF COMPETENCE, WORK PLACEMENT AND CAREER DEVELOPMENT ON THE PERFORMANCE OF CIVIL SERVANTS AT THE DEPARTMENT OF INDUSTRY AND TRADE MALUKU PROVINCE - Daniella Mirella Tahalele; Novalien Carolina Lewaherilla; Ferdy Leuhery (SEAN Institute, 2023)
This study aims to determine the effect of competence, job placement and career development on the performance of Civil Servants at the Office of Industry and Trade of Maluku Province. Methods This research uses survey research methods and explanatory research types. The population in this study were 80 employees of the Maluku Province Industry and Trade Office, and the sample used in this study were 48 civil servants. Data collection techniques using a questionnaire. The data analysis method used is multiple linear regression analysis with SPSS v 26 (2023). The results of the study show that partially competence has a significant effect on performance, partially work placement has a significant effect on performance, partially career development has no significant effect on performance. For further research it is suggested to be able to study other variables that can affect performance